2022
DOI: 10.21203/rs.3.rs-2033818/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detection of spontaneous neutral kaons K0L and K0s from ultra-dense hydrogen H(0)

Abstract: We here report muon and gamma photon signatures from decay of neutral kaons K0L and K0sto complement the published results of kaon generation from laser-induced baryon annihilation in H(0) (Holmlid and Olafsson, High Energy Density Physics 2021, and Holmlid, International Journal of Hydrogen Energy 2021). One well-known complication in the kaon detection is the oscillation process between the neutral kaons K0L and K0s caused by interaction with matter. Particle energy measurements with plastic scintillators id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The experimental setup includes a two-beam Q-switched Nd:YAG laser and the following components: a UHV chamber (1), a turbomolecular pump (2), a time-of-flight tube (3), a Faraday detector (4), a sensor flange (5), a beam alignment view port (6), XYZ motion manipulation (7), a laser view-port lens (8), an ultrafast laser diode (9), an oscilloscope (10), the hydrogen and gas line, the hydrogen Rydberg state catalyst (13), a laser target (14), and a radiation detector (15).…”
Section: Figmentioning
confidence: 99%
“…The experimental setup includes a two-beam Q-switched Nd:YAG laser and the following components: a UHV chamber (1), a turbomolecular pump (2), a time-of-flight tube (3), a Faraday detector (4), a sensor flange (5), a beam alignment view port (6), XYZ motion manipulation (7), a laser view-port lens (8), an ultrafast laser diode (9), an oscilloscope (10), the hydrogen and gas line, the hydrogen Rydberg state catalyst (13), a laser target (14), and a radiation detector (15).…”
Section: Figmentioning
confidence: 99%
“…Most studies using this source have employed a pulsed laser to transfer H(0) from state s = 2 to s = 1, but some studies have instead observed the spontaneous process [29,40] which creates mesons, muons and gamma photons. The induced and spontaneous processes appear so far to be quite similar, even if they seem to take place in different parts of the H(0) layer.…”
Section: The Meson Sourcementioning
confidence: 99%
“…The 60 ns decay could be due to a pion with 319 MeV kinetic energy, but this does not fit well into any reasonable annihilation model. In other experiments [40], kaon creation is further tested by looking for gamma photons from neutral kaon decays. High-energy gamma photons were observed, but due to their high energy, an accurate calibration has not yet been possible.…”
mentioning
confidence: 99%